6h+7k-9(3h-6k)=

Simple and best practice solution for 6h+7k-9(3h-6k)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6h+7k-9(3h-6k)= equation:


Simplifying
6h + 7k + -9(3h + -6k) = 0
6h + 7k + (3h * -9 + -6k * -9) = 0
6h + 7k + (-27h + 54k) = 0

Reorder the terms:
6h + -27h + 7k + 54k = 0

Combine like terms: 6h + -27h = -21h
-21h + 7k + 54k = 0

Combine like terms: 7k + 54k = 61k
-21h + 61k = 0

Solving
-21h + 61k = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-61k' to each side of the equation.
-21h + 61k + -61k = 0 + -61k

Combine like terms: 61k + -61k = 0
-21h + 0 = 0 + -61k
-21h = 0 + -61k
Remove the zero:
-21h = -61k

Divide each side by '-21'.
h = 2.904761905k

Simplifying
h = 2.904761905k

See similar equations:

| 5x+5+7x-15=2 | | 13=2t | | g+15=3 | | -8x^6-24x^5+224x^4= | | 4.2x+59.5=28.5-11.3x | | (5x^2+3x-2)+(2x^2+5x+19)-(7x^2-10)= | | (8+1x)*m=5m | | 100x=80 | | 20x-1/2x^2=50 | | -1/4*8 | | 17x=6800 | | 3-1/4x=x-7 | | 12b^2-21=0 | | 8(z-12)=3(2z+4) | | r^2+6rg-16g^2= | | 14-z=8 | | W-4= | | x + 14 x = 10 | | 40,000*90,000,000= | | 11/(12-8*3)+4 | | b^2+3b+88= | | v=3.14rh^2 | | 12x-19=2x+1 | | -9=-6y+3(y-8) | | 7.1+5-6.1=6 | | 3x-5i=xi | | 3(2x+1)=31/3 | | 63/-3 | | 440/60= | | 2+3ln(2x)=20 | | 7x+9=59+2x | | z+12z-48=0 |

Equations solver categories